pH effects on growth and lipid accumulation of the biofuel microalgae Nannochloropsis salina and invading organisms - Bartley, Meridith L; Boeing, Wiebke J; Dungan, Barry N; Holguin, F. Omar; Schaub, Tanner (Journal of applied phycology, 2014)
Biofuels derived from non-crop sources, such as microalgae, offer their own advantages and limitations. Despite high growth rates and lipid accumulation, microalgae cultivation still requires more energy than it produces. Furthermore, invading organisms can lower efficiency of algae production. Simple environmental changes might be able to increase algae productivity while minimizing undesired organisms like competitive algae or predatory algae grazers. Microalgae are susceptible to pH changes. In many production systems, pH is kept below 8 by CO₂ addition. Here, we uncouple the effects of pH and CO₂ input, by using chemical pH buffers and investigate how pH influences Nannochloropsis salina growth and lipid accumulation as well as invading organisms. We used a wide range of pH levels (5, 6, 7, 8, 9, and 10). N. salina showed highest growth rates at pH 8 and 9 (0.19 ± 0.008 and 0.19 ± 0.011, respectively; mean ± SD). Maximum cell densities in these treatments were reached around 21 days into the experiment (95.6 × 10⁶ ± 9 × 10⁶ cells mL⁻¹ for pH 8 and 92.8 × 10⁶ ± 24 × 10⁶ cells mL⁻¹ for pH 9). Lipid accumulation of unbuffered controls were 21.8 ± 5.8 % fatty acid methyl esters content by mass, and we were unable to trigger additional significant lipid accumulation by manipulating pH levels at the beginning of stationary phase. Ciliates (grazing predators) occurred in significant higher densities at pH 6 (56.9 ± 39.6 × 10⁴ organisms mL⁻¹) than higher pH treatments (0.1–6.8 × 10⁴ organisms mL⁻¹). Furthermore, the addition of buffers themselves seemed to negatively impact diatoms (algal competitors). They were more abundant in an unbuffered control (12.7 ± 5.1 × 10⁴ organisms mL⁻¹) than any of the pH treatments (3.6–4.7 × 10⁴ organisms mL⁻¹). In general, pH values of 8 to 9 might be most conducive to increasing algae production and minimizing invading organisms. CO₂ addition seems more valuable to algae as an inorganic carbon source and not as an essential mechanism to reduce pH.